Application of Digital Find Me Pair Evaluation on Student Learning Outcomes of Class V Social Sciences Learning Cultural Diversity Material Elementary School - Annisa Dwi Rahmawati; Wahyu Susiloningsih (Journal of Education and Teacher Training Innovation, 2024)
This research is motivated by the low learning outcomes in social studies learning. So the learning outcomes of class V students are low and can be said to be insufficient (KKM). By implementing the Find Me Pair digital evaluation. The aim of this research is to describe the application of digital find me pair evaluation on the learning outcomes of students learning social sciences material on cultural diversity in class V elementary schools. This research includes descriptive quantitative research. Data collection in this research consisted of 30 students in the VA class at SDN Sedatigede II. The data collection method used is observation using an assessment tool in the form of an observation sheet and a test using an assessment tool in the form of a test sheet. The results of this research show that student activities and educator activities in implementing digital evaluation are in the very good category and student learning outcomes are in the very good category